VALIDITAS KONSTRUK INSTRUMEN ADAPTASI KUESIONER SUMBER DAYA SEKOLAH - Husain Abdul Rahman (STKIP Andi Matappa, 2023)
This research aims to test the construct validity of the adapted Resource Management Questionnaire Instrument, which was developed to measure examining resource management in Muhammadiyah private junior high schools in the Makassar City. The researchers used Confirmatory Factor Analysis and several fit indices, including Normed Chi-square, RMSEA, Standardized RMR, NFI, NNFI, and CFI, to evaluate the overall fit of the model. The standardized factor loadings and t-Values were used to provide evidence of the construct validity of the instrument. All of the 30 items in the questionnaire, had factor loadings greater than 0.4 and t-Values greater than 1.96.